Management of the Neck in Thick-Skinned Patients - Espinosa, Jorge; Valencia, Diana Parra (Facial Plastic Surgery, 2013)
The neck has always been one of the most difficult areas to manage in rejuvenation surgery. Even patients with adequate results after a facelift may be dissatisfied because of the appearance of the neck. Moreover, not all neck problems are the same in all patients. Some cases only require fat removal to obtain good results, whereas others require complete neck- and facelift to achieve the desired results. This article offers a detailed step-by-step description of the approach to aesthetic pathologies of the neck, tailored to the needs of each individual patient. The article also includes a discussion of topics such as double chin liposuction, platysma plication, corset platysmaplasty, platysmal suspension to the mastoid, mentoplasty, and neck- and facelift.
Keywords: neck lift; neck rejuvenation; aging neck surgery; neck liposuction